Evaluation of the Implementation of Urban Waste Management Technology Policy : Study Area in Depok City - Deny Kartika; Jenni Ria Rajagukguk; Fathir Fajar Sidiq; Kartika Syskya Wydya (Universitas Pancasakti Tegal, 2026)
Urban waste management in Depok faces increasing challenges due to rapid population growth and inadequate infrastructure, with waste production estimated to reach 70 million tons nationally by 2025. This requires innovation in local governance technology and socio-economic realities. This review synthesizes the literature on policy coherence, community participation, and the adoption of Smart Waste Management Systems (SWMS), the Internet of Things (IoT), and artificial intelligence applications. Findings indicate that although digital tools and smart technologies offer the potential for increased efficiency, their integration is still limited by deficiencies in infrastructure, data governance, and institutional coordination. Studies emphasize the crucial role of community-based initiatives and participatory governance in achieving sustainable outcomes, particularly through education and public awareness programs that promote the 3R (Reduce, Reuse, Recycle) principles. Economic analysis also highlights opportunities in waste-to-energy conversion technologies and waste-to-fuel systems to support financial sustainability. However, socioeconomic inequality and limited inclusion of marginalized communities hinder equitable implementation. This review concludes that Depok's success in waste management depends on harmonizing technological advances with inclusive governance, consistent long-term policies, and community empowerment. Therefore, theoretical contributions through a multifaceted approach that combines innovation, regulation, and social engagement are essential to building a resilient, sustainable, and equitable urban waste management system that can adapt to future environmental challenges.